Ion beam analysis of Heusler alloy Fe3Si epitaxially grown on Si(111). Issue 11 (12th September 2014) - Maeda, Yoshihito; Kawakubo, Yuki; Noguchi, Yuya; Narumi, Kazumasa; Sakai, Seiji; Pizzini, Sergio; Kissinger, Gudrun
Abstract We have investigated atomic ordering of Heusler alloy Fe3Si(111) epitaxially grown on Si(111) by using ion beam analysis. The total atomic displacement along Si<111> directions was deduced from the minimum yield χmin and the critical angle Ψ1/2 for channeling. The total displacement consists of both one‐dimensional thermal vibrations computed by the Debye theory and static displacements due to imperfections, lattice mismatch, thermal expansion etc. The atomic displacement increased as the annealing temperature increased from 373 to 573 K. We found that this static displacement came from a difference in thermal expansion between the Fe3Si film and Si substrates at the anneal temperature and was quenched into room temperature as a remnant displacement. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)